The Effect of Health Education Through Animated Videos on Preventive Knowledge and Attitudes Obesity in Adolescents of SMPN 8 Malang - Kamiliatun Nisa'; Atti Yudiernawati; Sugianto Hadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: In Indonesia, obesity is becoming a growing health problem. Not only do many cases of obesity or overnutrition occur in adulthood, but it also often occurs in adolescence. through the use of visually appealing, easily available, and youth-specific media - specifically animated videos - to promote health and prevent obesity. Animated images are a series of still photographs displayed at a specific time to give the impression that the images are moving. In other words, animation is the movement of objects to give a more dynamic and captivating appearance. The use of animated features on instructional videos can grab the attention of the audience and encourage more thought-provoking questions from them, which will reduce their cognitive load. Objective: This study was conducted with the aim of determining the effect of health education using animated videos on increasing knowledge and attitudes towards obesity prevention in adolescents at SMPN 8 Malang. By evaluating the impact of animated video interventions, the research seeks to provide insights into the effectiveness of multimedia educational tools in enhancing students' understanding and fostering positive attitudes towards maintaining a healthy weight and preventing obesity. Methode: The type of research used was quantitative research with one group pre-post design with a sample of 31 adolescents. Knowledge data collection techniques used a questionnaire and attitude data collection using a checklist sheet. Knowledge of adolescents before education through animated videos found that most (52%) adolescents had sufficient knowledge. Result: After education through animated videos, it was found that almost all (93.5%) adolescents had good knowledge. The attitude of adolescents before education through animated videos was found that most (71%) adolescents had a negative attitude. After being given education, most (61%) adolescents have a positive attitude. The results of the Wilcoxon test knowledge obtained a significant value of p-value 0.000 < ? (0.05) and attitude obtained a significance value of p-value 0.000 < ? (0.05) this shows that there is an effect of education using animated videos on the knowledge and attitudes of adolescents about obesity prevention. Conclussion: This study proves that there is an effect of education through animated videos on the knowledge and attitudes of obesity prevention in adolescents at SMPN 8 Malang. at SMPN 8 Malang animated video media can be one of the media in increasing the knowledge and attitudes of adolescents SMPN 8 Malang in obesity prevention.